Striking subgroup differences in substance-related mortality after release from prison - Forsyth, S.; Alati, Rosa; Ober, C.; Williams, G.; Kinner, S. (Wiley-Blackwell Publishing Ltd., 2014)
© 2014 Society for the Study of Addiction. AIMS: To compare the incidence, timing and risk factors for substance-related death between Indigenous and non-Indigenous ex-prisoners in Queensland, Australia.DESIGN: Retrospective cohort study.SETTING: All adult prisons in the state of Queensland, Australia, linked to deaths registered in Australia.PARTICIPANTS/CASES: We obtained records for all adults released from prison in Queensland, Australia from 1 January 1994 to 31 December 2007. Among this cohort of 42?015 individuals we observed 82?315 releases from prison and 2158 deaths in the community by the end of 2007, of which 661 were substance-related deaths.MEASUREMENTS: Incarceration data were obtained from Queensland Corrective Services and linked probabilistically with deaths recorded in the Australian National Death Index.FINDINGS: In the first year after release, Indigenous ex-prisoners were more likely to die from alcohol-related causes [hazard ratio (HR)?=?1.9, 95% confidence interval (CI)?=?1.1-3.1)] but less likely to die of drug-related causes (HR?=?0.34, 95%CI?=?0.21-0.53) than were non-Indigenous ex-prisoners. Among non-Indigenous prisoners only, the risk of substance-related death was significantly higher in the first 4 weeks [relative risk (RR)?=?5.1, 95% CI?=?3.7-6.9] when compared with the risk after 1 year post-release. Most evaluated risk factors for substance-related death were similar for Indigenous and non-Indigenous ex-prisoners; however, the hazard of death increased with age more for Indigenous ex-prisoners (HR?=?1.7 per decade of age, 95% CI?=?1.4-2.1) than for non-Indigenous ex-prisoners (HR?=?1.3, 95% CI?=?1.2-1.4).CONCLUSIONS: In Australia, patterns of substance-related death in ex-prisoners differ markedly according to Indigenous status. Efforts to prevent substance-related deaths in ex-prisoners should consider heterogeneity in the target population and tailor responses accordingly.